If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1(-30s) = 465 Remove parenthesis around (-30s) 15 + -1 * -30s = 465 Multiply -1 * -30 15 + 30s = 465 Solving 15 + 30s = 465 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 30s = 465 + -15 Combine like terms: 15 + -15 = 0 0 + 30s = 465 + -15 30s = 465 + -15 Combine like terms: 465 + -15 = 450 30s = 450 Divide each side by '30'. s = 15 Simplifying s = 15
| 3(x-1)4+7=19 | | 2s-3=9 | | Y=ln(1-x^2) | | Y=(18-9)*p | | x=23+9 | | 3=16x+15 | | 17-2(1-3x)4=5 | | h(-3)=-3 | | 8(-3n-7)+6(6+4n)=-24 | | -9h+32=-67 | | 5-m=131 | | 11x^2=5x-3 | | 16+3x=7x-3 | | 4x^3+5x^2+2x+16=X+2 | | 10x+15+6x-11=180 | | 3x^2+5x=16 | | 4x^3+5x^2+2x+16= | | 3x*2+5x=16 | | 36=-3(k-6) | | y=-0.05x^2+1.25x | | 3(2x+9)=-15 | | 3(w-11)=15 | | 18z-17z+3=17 | | 10-2r=6 | | -6.8(2p+5)-1.6(4p+6)= | | T=24m-4m^2 | | 16=4(n+1) | | h(-4)=-5 | | ix^2-8x+30=0 | | (7x^4+xy^2)dx+(x^2y+6y^5)dy=0 | | x=172+-3x | | 8(x+6)-24=4(2x+5) |